(untitled) (Eesti Arst, 2007)
Total hip arthroplasty with cemented Lubinus SP II prosthesis is well analyzed in the Sweden National Hip Arthroplasty Register. There are only few reports from the other countries concerning survival analysis of this implant in short and mid-term follow-up. Eesti Arst 2007; 86(8):533-602